Charge-functionalized and mechanically durable composite cryogels from Q-NFC and CS for highly selective removal of anionic dyes. (15th October 2017) - Chen, Yufei; Ru, Jing; Geng, Biyao; Wang, Haiying; Tong, Congcong; Du, Chungui; Wu, Shengchun; Liu, Hongzhi
Highlights: A novel aerogel-type adsorbent for anionic dyes was elaborated from Q-NFC and CS. The mechanical durable aerogel displays superior adsorption properties. The aerogel was able to effectively separate anionic dyes from cationic ones. The biobased aerogel can be readily reused with no loss of adsorption capacities. Abstract: A composite cryogel was prepared from quaternized nanofibrillated cellulose (Q-NFC) and chitosan (CS) through a combination of freeze-drying and cross-linking with epichlorohydrin. The specific surface area of the composite cryogel was approximately two times that of Q-NFC cryogel. And the composite cryogel exhibited superior adsorption properties of anionic dyes than either the Q-NFC or CS cryogel controls. The adsorption isotherm well fitted the Langmuir model with the maximum theoretical adsorption capacity up to 473.9 mg/g. The adsorption behavior was found to follow pseudo second-order kinetic model, indicating the chemisorption nature. Notably, the composite cryogel could effectively separate the cationic dye from anionic one. Furthermore, the composite cryogel displayed excellent reusability, evidenced by the removal percentage of Acid red 88 still as high as 96% even after five adsorption-desorption cycles. These advantages would make it an environmentally friendly candidate for the use in the separation and efficient removal of anionic dyes.